ANALISIS HUKUM TERHADAP KASUS MALPRAKTIK MEDIS PADA BALITA DI BIMA - Elita, Carlene Amalia; Salsabilla, Islama A’la Syifa; Ramadhani, Novalina Rizka Brillian; Ismawati, Rusida; Ramadhani, Zulfa Rozin (Universitas Stikubank, 2026)
The case of medical malpractice involving a toddler in Bima has attracted public attention and raised the urgency of evaluating legal accountability mechanisms in healthcare. This study aims to analyze the law enforcement process and the forms of legal responsibility that can be imposed on medical personnel and healthcare institutions suspected of involvement. Using a normative juridical approach, this study examines relevant laws, doctrines, and legal literature, including provisions in the Medical Practice Law, the Health Law, the Hospital Law, and the Criminal Code. The results indicate that law enforcement in malpractice cases can be pursued through administrative, civil, and criminal channels, depending on the level of negligence and the resulting consequences. Medical personnel can be held personally liable for violations of professional standards, while healthcare institutions can be held accountable based on the principle of vicarious liability. This study concludes that the case in Bima underscores the importance of strengthening regulations, improving medical service standards, and ensuring transparency in law enforcement to protect patient rights, particularly children.